INFLUENCE OF PHYSICAL CULTURE ON THE FORMATION OF PERSONAL CHARACTERISTICS AND QUALITIES - Rakhimkulov Karimjon Datkaevich (American Journals Publishing, 2023)
The physical culture of a person is inextricably linked with his general culture, since the characteristics characteristic of a physically cultured person are formed and developed on the basis of the same psychophysical (natural) tendencies and psychophysical processes, such as moral, aesthetic and psychophysical processes. other types of human culture. Therefore, when performing physical exercises, a person not only develops and improves his physical abilities, but also forms other personal qualities - moral, aesthetic, as well as courage, will, initiative, tolerance, etc. This article highlights the impact of physical education on the formation of traits and personality traits.
Keywords: Physical education, spiritual culture, personality traits, spiritual spheres, all-round development.